Liver and Steroid Hormones—Can a Touch of p53 Make a Difference? - Charni-Natan, Meital; Aloni-Grinstein, Ronit; Osher, Etty; Rotter, Varda (Frontiers in Endocrinology, 2019)
The liver is the main metabolic organ in the body, serving as a significant hormonal secretory gland and functioning to maintain hormone balance and homeostasis. Steroid hormones regulate various biological pathways, mainly in the reproductive system and in many metabolic processes. The liver, as well as steroid hormones, contribute significantly, through functional intertwine, to homeostasis maintenance and proper responses during stress. Malfunction of either has a significant impact on the other and may lead to severe liver diseases as well as to several endocrine syndromes. Thus, the regulation on liver functions as on steroid hormones levels and activities is well controlled. p53, the well-known tumor suppressor gene, was recently found to regulate metabolism and general homeostasis processes, particularly within the liver. Moreover, p53 was shown to be involved in steroid hormones regulation. In this review, we discuss the bi-directional regulation of the liver and the steroid hormones pointing to p53 as a novel regulator in this axis. A comprehensive understanding of the molecular mechanisms of this axis may help to prevent and treat related disease, especially with the increasing exposure of the population to environmental steroid hormones and steroid hormone-based medication.